THE EFFECT OF INFECTION OF MYCOBACTERIUM TUBERCULOSIS STRAIN H37RV TOWARDS THE EXPRESSION OF TNF- α IN THE BRAIN - Santoso, Giovani Anggasta; Sujuti, Hidayat; Hidayati, Dwi Yuni Nur (Malang Neurology Journal, 2017)
Background. Tuberculosis caused by mycobacterium tuberculosis. The support of these inflamated factors contained in this focus determine the prognosis of TB towards Central Nervous System. One of the inflammation factors is TNF-α.Objective. To find the expression of TNF-α on the brain which are infected by M. tuberculosis.Methods. Experimental study, Wild Mus musculus to compare the group which has got infected before. The similiar study has been conducted by Laksmi Wulandari, pulmonologist. The observation towards the expression of TNF-a into a mouse’s brain was done by using the imunohistokimia method. It is marked by the brown color in the core, sitoplasma and the cell with upgrading size 100x times 20.Results. This is evident that significanly corelation (P = 0.000) between independent Mycobacterium tuberculosis infection at incubation periode 8 and 16 weeks) and dependent variabel (TNF-α expression on brain winstar tissue that infected by Mycobacterium tuberculosis for 8 and 16 weeks).Conclusion. Strong relationship between expression of TNF-a and the M. Tuberculosis’ infection.